2022
DOI: 10.3390/plants11030313
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Alter Microtubule Arrangement, Dynamics and Stress Phytohormone Levels

Abstract: The superior properties of silver nanoparticles (AgNPs) has resulted in their broad utilization worldwide, but also the risk of irreversible environment infestation. The plant cuticle and cell wall can trap a large part of the nanoparticles and thus protect the internal cell structures, where the cytoskeleton, for example, reacts very quickly to the threat, and defense signaling is subsequently triggered. We therefore used not only wild-type Arabidopsis seedlings, but also the glabra 1 mutant, which has a diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…40 Recent research has shown that these defense hormones can be directly involved in the reaction of plants to nanoparticle stress. 5,41 Abiotic stresses like drought, salinity and extreme temperature, does not directly cause an immune response. Nonetheless, abiotic stress can also induce resistance in plants.…”
Section: Response To Stress and Defense: Immunity-related Signaling P...mentioning
confidence: 99%
See 2 more Smart Citations
“…40 Recent research has shown that these defense hormones can be directly involved in the reaction of plants to nanoparticle stress. 5,41 Abiotic stresses like drought, salinity and extreme temperature, does not directly cause an immune response. Nonetheless, abiotic stress can also induce resistance in plants.…”
Section: Response To Stress and Defense: Immunity-related Signaling P...mentioning
confidence: 99%
“…Different pathogen species can cause different responses of these hormones, for example, due to distinct herbivore feeding strategies: piercing and sucking pests, such as aphids, primarily trigger SA and JA pathways, whereas the JA pathway predominantly mediates the responses to chewing herbivores . Recent research has shown that these defense hormones can be directly involved in the reaction of plants to nanoparticle stress. , …”
Section: Response To Stress and Defense: Immunity-related Signaling P...mentioning
confidence: 99%
See 1 more Smart Citation
“…swollen chloroplast structure, fewer thylakoids, abnormal size of plastoglobules and starch granules, destructive changes in peroxisomes, swollen mitochondrial cristae, and condensed nucleus) have been described (recently reviewed by Rajput et al , 2019 ). Furthermore, the intracellular presence of NM can also affect the copy number of chloroplast and mitochondrial DNA ( Pagano et al , 2022 ), as well as the number and growth rate of the microtubule component of the cytoskeleton ( Angelini et al , 2022 )…”
Section: Nanomaterials Affect Plants At the Cellular And Subcellular ...mentioning
confidence: 99%
“…Plant growth and morphogenesis change due to disturbed microtubule organization in A. thaliana which suffered from UV-B radiation [ 6 , 26 ]. Microtubule reorganization and corresponding morphology caused by stress are connected with cellular signals, such as nitric oxide [ 6 , 24 , 27 ], brassinosteroid [ 28 ], and ABA [ 29 , 30 ]. It is essential to comprehensively investigate the effects of UV-B radiation on plant growth and the relations of hormone signals and microtubule cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%